LEXICAL PROBLEMS OF TRANSLATING THE NAMES OF NEW PHENOMENA IN MASS MEDIA - Teshabayeva, Dilfuza (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This study explores the nuanced challenges of translating English to Russian, highlighting the importance of cultural, contextual, and linguistic considerations. It emphasizes the role of translators as cultural mediators and the complexity of conveying socio-political content accurately, underscoring the dynamic interplay between languages and the necessity for a multifaceted approach to translation.